2006
DOI: 10.1007/s10238-006-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline comet assay study with breast cancer patients: evaluation of baseline and chemotherapy-induced DNA damage in non-target cells

Abstract: The sensitivity of the alkaline comet assay for the evaluation of baseline and treatment-induced DNA damage in white blood cells of breast cancer patients receiving adjuvant chemotherapy according to three conventional anthracycline- and cyclophosphamide-containing protocols was investigated. Additionally, baseline DNA damage in cancer patients was compared with the levels of DNA damage recorded in healthy women. Altogether 30 patients with diagnosed breast cancer and 30 female blood donors with no known famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
4
21
1
2
Order By: Relevance
“…A significant increase in DNA damage was observed in all post-treatment samples when compared to pre-treatment samples. This finding is in agreement with previous reports, 5,15,27,37 which have indicated that the administration of antineoplastic drugs and radiotherapy are accompanied by significant DNA damage to nucleated blood cells. The previous data and the present results support the usefulness of the comet assay as a sensitive technique to evaluate damage caused by radiotherapy or chemotherapy.…”
Section: A U T H O R P R O O Fsupporting
confidence: 94%
See 2 more Smart Citations
“…A significant increase in DNA damage was observed in all post-treatment samples when compared to pre-treatment samples. This finding is in agreement with previous reports, 5,15,27,37 which have indicated that the administration of antineoplastic drugs and radiotherapy are accompanied by significant DNA damage to nucleated blood cells. The previous data and the present results support the usefulness of the comet assay as a sensitive technique to evaluate damage caused by radiotherapy or chemotherapy.…”
Section: A U T H O R P R O O Fsupporting
confidence: 94%
“…9,10 In several studies, the authors did not find an association between age and DNA damage when using the comet assay. 5,28,29,35,36 In the present study, no association between levels of DNA damage and age (> 50 years or ≤ 50 years) was found.…”
Section: A U T H O R P R O O Fcontrasting
confidence: 59%
See 1 more Smart Citation
“…Results indicated that even exposure to low concentrations of antineoplastic drugs might affect these drugs are often used in combination, in order to achieve additive and/or synergistic effects on tumour cells resulting from their differing modes of action. However, most, if not all, of these chemical agents are generally nonselective and along with tumour cells, normal cells may undergo cyto/genotoxic damage (26,(36)(37)(38)(39).…”
Section: Antineoplastic Drugs In Cancer Treatmentmentioning
confidence: 99%
“…However, if unrepaired, DNA lesions may give rise to chromosome aberrations, which are able to interfere with the transcription and replication of DNA, resulting in cytotoxic and mutagenic effects. Due to all these characteristics, growing evidence suggests that secondary neoplasms may arise as a consequence of chemotherapy (37,(40)(41)(42)(43).…”
Section: Antineoplastic Drugs In Cancer Treatmentmentioning
confidence: 99%